COMPUTER SCIENCE, COMPUTER ENGINEERING AND MANAGEMENT METHODICAL APPROACH TO EVALUATING THE PROBABILISTIC TIME PERFORMANCE INDICATOR OF AUTOMATED ADMINISTRATOR OPERATIONS IN INFORMATION PROTECTION SYSTEMS - A. M. Kadnova (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives At present, in accordance with the requirements of the guiding documents of the Federal Service for Technical and Export Control (FSTEC) of Russia, as well as international standards in the development and operation of protected automated systems, it is necessary to evaluate the effectiveness (general utility) of information protection systems. The article is devoted to the development of a method for assessing the ergotechnical characteristics of software information security systems for use the assessment of the general utility of such systems. The aim of the work is to develop a methodology for assessing the probabilistic indicator of the timeliness of typical operations for the administration of information security systems.Method To achieve this goal, user groups were created in order to perform typical administrative operations within the information protection system. The operation time for each group, recorded using the IOGraphV1.0.1 tool, was utilised to calculate the probabilities of timely execution of typical operations by the administrator according to a truncated normal distribution formula.Results An assessment of a probabilistic indicator was carried out in order to evaluate the timeliness of operations performed by the administrator of the information protection system.Conclusion The results can be used in a comprehensive assessment of the effectiveness (reliability) of the automated functioning of information security software systems when modelling and analysing the security of special-purpose informatisation facilities.